Laparoscopic resection for colorectal diseases: short-term outcomes of a single center - (:unkn) unknown (AVES, 2016)
Objective: Even though, laparoscopy is not accepted as the current gold standard in colorectal surgery, it can be performed as safely as open surgery. It is also widely accepted that the technique has many advantages. In this study, we evaluated the results of 33 patients with laparoscopic colorectal resection. Material and Methods: Thirty-three patients who underwent laparoscopic colon surgery between January 2013 and September 2014 in the General Surgery Clinic at Marmara University Hospital were included in the study. Patients were evaluated in terms of their demographic and tumor histopathologic characteristics, type of surgery and early postoperative complications. Results: Laparoscopic colorectal resection was performed for 33 patients who had malignant or benign lesions. The median age was 60 (35-70), and 18 (55%) were male patients. The majority of the patients (90%) were diagnosed with colorectal adenocarcinoma. Half of the patients were T3 and 67% had N0 stage. The median number of retrieved lymph nodes was 17 (4-28). Negative surgical margins were obtained in all patients. The postoperative hospital stay was 5 (4-16) days. Postoperative early complications were observed in only 5 patients. The majority of complications were treated without the need for surgery. No mortality was recorded in this series of patients. Conclusion: This study showed that laparoscopic colorectal surgery could be performed safely based on its low complication rate, short length of hospital stay, providing sufficient surgical resection and lymph node dissection.
Keywords: Laparoscopy; colorectal surgery; colon resection; OPEN COLECTOMY; COLON-CANCER; SURGERY; TRIAL